2009
DOI: 10.1039/b905239a
|View full text |Cite
|
Sign up to set email alerts
|

Substituent-dependent exchange mechanisms in highly fluxional RSn93− anions

Abstract: 119Sn NMR studies show that the RSn9(3-) ions (R=i-Pr, Sn(C6H11)3) are highly fluxional in solution, where the exchange mechanisms involve rapid migration of the R group in the latter but not in the former.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 20 publications
1
39
0
6
Order By: Relevance
“…This sharp singlet is indicative of whizzing of the Ph 3 Sn moiety about the cyclo-P 3 ring. 1,[10][11][12] Variable temperature NMR spectra obtained as low as −90 • C reveal no locking out of this movement on the NMR time scale.…”
mentioning
confidence: 99%
“…This sharp singlet is indicative of whizzing of the Ph 3 Sn moiety about the cyclo-P 3 ring. 1,[10][11][12] Variable temperature NMR spectra obtained as low as −90 • C reveal no locking out of this movement on the NMR time scale.…”
mentioning
confidence: 99%
“…[23] NMR studies: As previously reported, [38] (Table 3). While the solid-state structure shows that the SnCy 3 exo group is attached to the upper waist of a distorted C 4v -type cluster (Scheme 1), the SnCy 3 moiety does an intramolecular walk around the Sn 9 cluster in solution, while the Sn 9 cluster simultaneously undergoes a diamond-square-diamond exchange that time-averages all nine vertex atoms.…”
Section: Introductionmentioning
confidence: 83%
“…[26][27][28][29][30][31][32] In particular, the [ 3À clusters, wherein R is an exo-bonded alkyl or posttransition metal group, have been prepared by nucleophilic substitution reactions. [33][34][35][36][37][38] Unlike the multicenter two-electron bonding within the E 9 clusters, the exo substituents are attached to the clusters through two-center, two-electron bonds. The substituents are known to affect the solubilities [25,35] and dynamic properties of the clusters, [38] but the reactivities of these ions have not been studied in detail.…”
Section: A C H T U N G T R E N N U N G [Ni@ge 9 ] 3à !A C H T U N G Tmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Notable milestones are the oxidative coupling of Ge9 4-clusters to oligomers and infinite chains, 7-19 their metallation, [14][15][16][20][21][22][23][24][25] capping by transition-metal organometallic fragments, 26-34 insertion of a transition-metal atom at the center of the cluster which is sometimes combined with capping and oligomerization, 35-47 addition of main-group organometallic fragments as exo-bonded substituents, 48-50 and functionalization with various organic residues by reactions with organic halides and alkynes. [51][52][53][54][55][56][57][58] This latter development of attaching organic fragments directly to the clusters has opened up a new field, namely organo-Zintl chemistry, that is potentially fertile for further synthetic explorations, and it is the step-by-step procedure for the synthesis of germanium-divinyl clusters described herein. The initial steps outline the synthesis of an intermetallic precursor of K4Ge9 from which the Ge9 4-clusters are extracted later in solution.…”
Section: Introductionmentioning
confidence: 99%